Penguatan Kepemimpinan Visioner Dan Pengembangan Kepribadian Dalam Upaya Peningkatan Kreativitas Guru - Adawiah, Siti Asiah; Suharyati, Henny (Universitas Pakuan, 2024)
STRENGTHENING VISIONARY LEADERSHIP AND PERSONALITY DEVELOPMENT IN AN EFFORTS TO INCREASE TEACHER CREATIVITYTeachers are one of the components of education that aims to achieve the ten profiles of Indonesian humans by the law. However, teachers' creativity in permanent private high school foundation teachers an Accredited ”A” in Bekasi regency is still not optimal. Therefore, this research analyzes the relationship between visionary leadership personality development and teacher creativity. The method used in this research is a survey method with a correlation approach. This research was conducted at 18 private Islamic high schools accredited